Health checks on patients 75 years and over in Nottinghamshire after the new GP contract. Issue 6854 (12th September 1992) - Brown, K.; Williams, E. I.; Groom, L.
Abstract : OBJECTIVE--To investigate annual health checks for patients of 75 years and over required by the 1990 contract for general practitioners. DESIGN--Visits to practices to collect information on how assessments were organised and carried out; completion of questionnaires for every patient who had been assessed in a sample month, using information provided by the practice records. SETTING--20 general practices in one family health services authority. SUBJECTS--Patients of 75 years and over in 20 general practices. RESULTS--Three practices (15%) had not performed checks. Thirteen practices sent a letter to invite patients to undergo a check. Of these practices, seven followed up non-responders. Two practices visited patients' homes unannounced, and two did checks on an opportunistic basis only. Sixteen practices used a checklist. Sixteen practices involved their practice nurses; at eight of these, doctors also performed checks; in six practices the nurses undertaking the checks had no training in assessing old people. Ten practices assessed more than 75% of their old people in the first year of the new contract. Practices that did not follow up patients who had not responded to the invitation for assessment completed significantly fewer checks. During the sample month, 331 patients were assessed in the 17 practices. 204 new problems were discovered in 143 patients. Significantly more problems per patient were found in inner city areas. CONCLUSIONS--The way health checks were performed varied greatly, both in their organisation and the practices' attitudes. Many old people did not respond to letters asking if they wanted an assessment but very few refused one if followed up. Forty three per cent of those assessed had some unmet need. The number of new problems found per patient may reduce over the next few years if the assessments are successful. The need for annual assessment should be kept under review and adequate resources made available for the needs uncovered. Improved training for practice nurses in assessment is needed. Effectiveness of the checks must be monitored. If most unmet need falls in particular high risk groups it would seem sensible to modify the annual check to target these groups.